The Role of Argyrophilic Nucleolar Organizer Region (AgNOR) Study in Cytological Evaluation of Fluids, Especially for Detection of Malignancy - Karki, S; Jha, A; Sayami, G (Kathmandu University Medical Journal, 2012)
Background Serous effusion smears reported as “suspicious for malignancy” pose problems in clinical management. Silver staining for argyrophilic nucleolar organizer regions (AgNOR) has proved useful in making a cytopathologic differential diagnosis between benign and malignant cells. Nucleolar organizer regions(NORs) are loops of DNA located in acrocentric chromosomes. These NORs are visualized by silver staining technique that recognizes these argyrophilia associated proteins which are increased in malignancy. Objective This study aimed to distinguish reactive mesothelial cells from malignant cells in serous effusions using these NORs. Methods A total of 174 serous effusions received at the Department of Pathology, TUTH, during a period of one year were included in the study. Smears were studied by conventional Papanicolaou and Giemsa stains. AgNOR counts, variation in size and dispersion of AgNOR dots in smears were graded and compared in malignant and non-malignant effusions. Results Mean AgNOR counts of 10.43±0.73 and 10.21±0.51 in malignant peritoneal and pleural effusions, respectively, were significantly (p<0.0001) greater as compared with counts of 2.12±0.54 and 2.11±0.54 in non-malignant effusions. The AgNORs were irregular in shape in malignant effusions whereas they were comparatively larger, single dots in benign effusions. AgNOR size and dispersion were of higher grade in significantly greater proportion of malignant as compared with non malignant effusions (p<0.0001). Of the cytologically suspicious samples, nine were in the malignant range and one was in the benign range. Conclusion AgNOR study appears to be clinically useful as an additional diagnostic tool for use in serous effusion when the cytologic diagnosis is difficult. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 44-47 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6913